Integrated metabolome analysis and transcript profiles revealed a potential role of SWEETs in sugar accumulation during Carrot taproot development - Guanglong Wang; Yujie Xu; Jiaqi Wu; Yangyang Chen; Yahong An; Zhenzhu Hu; Aisheng Xiong (BMC Plant Biology)
Abstract Background Carrot is a root vegetable abundant in numerous nutritional values. Sugar is one of the most important carbohydrates in horticultural products that play important roles in plant growth and development and response to biotic and abiotic stresses. However, the dynamics of the metabolites including sugar during carrot root development still remain unclear. Here, the differential metabolites in carrot roots at different developmental stages were measured using an UPLC-ESI-MS/MS system. The accumulation profiles of metabolites, especially sugars, as well as the transcript patterns of Sugars Will Eventually be Exported Transporter (SWEET) genes were intensively examined. Results The results identified 727 metabolites over all the samples detected, of which, 539 metabolites were found to be differential accumulated. A total of 34 differentially accumulated sugar metabolites were identified over the period of root development. Furthermore, 17 DcSWEET genes were detected to be specifically expressed in the roots, indicating a potential for root enlargement and sugar accumulation in carrot root. Conclusions The results from the current study would help carrot breeding focused on yield and quality improvement.